Mr. Putter & Tabby : Take the train - Rylant, Cynthia; Howard, Arthur (San Diego, CA : Harcourt, 1998)
After a small setback, Mr. Putter and his favorite companions enjoy the best train ride of their lives.
Booklist
Elem. School Library Collection
School Library Journal
Booklist, November 1998
Elem. School Library Collection, June 2000
Kirkus Review, June 1998
Keywords: Cats -- Fiction; Dogs -- Fiction; Old age -- Fiction; Trains -- Fiction; Cats -- Fiction; Dogs -- Fiction; Old age -- Fiction; Railroads -- Fiction